Teologi Kerukunan Antar Umat Beragama Perspektif Farid Esack dan Relevansinya Terhadap Kehidupan di Indonesia - Ulummudin; Muhtar Solihin; Munir (Islamuna: Jurnal Studi Keislaman, 2025)
Religious plurality is a social reality that cannot be avoided in modern society. The diversity of beliefs often gives rise to challenges in building harmonious relationships among religious communities, especially when theological differences intersect with social and political interests. Therefore, a religious framework of thought is needed that can respond constructively to this plural reality and is oriented towards humanitarian values. This article aims to examine the concept of interfaith relations from the perspective of Farid Esack. The study focuses on how Esack views interfaith relations not merely as a form of passive tolerance but as active solidarity based on social justice. The results of the study show that Farid Esack develops a theological perspective that is contextual and aligned with oppressed groups. According to him, interfaith relations must be realized through concrete cooperation in addressing issues of injustice, poverty, and oppression. Interfaith solidarity is understood as an expression of shared moral responsibility that does not eliminate each faith's identity but rather strengthens the commitment to the values of justice and liberation. Thus, Farid Esack's thought makes an important contribution to the development of discourse on interfaith relations in plural societies, including Indonesia, which has diverse ethnicities, cultures, and religions.